Using Ant Colony Algorithm to solve NP-Complete problems - Abdul-Abbas , Waffa (University of Thi-Qar Journal of Science, 2011)
We consider the problem of scheduling jobs on a single machine about a common duedate. Our objective is to determine the common due date and processing sequence of new jobstogether with the re-sequencing of old jobs which minimize the sum of jobs’earliness/tardiness, completion time penalties and due date related penalty. We driveproperties that can be used to find the optimal common due date and processing sequence.Since our problem is NP-hard, we propose Ant colony algorithm (ACO) to solve the problemefficiently. Results from computational study reveal that Ant colony algorithm (ACO) can